The Influence of Education and Social Status on Dui Pappenre's Value: Family Financial Implications - Machmud, Mulyana; Syahril, Muh. Akbar Fhad; Kasim, Aksah (Amsir Management Journal, 2024)
This study examines the influence of education level and social status on determining the Dui Pappenre value and its implications for family finances in Bugis traditional marriages. Using a qualitative method with a case study approach, this study analyzes the financial impact of high Dui Pappenre values on the economic stability of men's families and the financial management strategies of young couples after marriage. The results show that high Dui Pappenre values impose a significant financial burden, causing decreased liquidity, increased debt, and reduced family investment capacity. Young couples implement financial management strategies, including detailed budgeting, spending priorities, systematic debt repayment efforts, and improving financial literacy. This study emphasizes the importance of a balance between preserving cultural traditions and family economic well-being and recommends constructive dialogue to adjust Dui Pappenre values to be more realistic with current economic conditions